Which Is Stronger? A Continuing Battle Between Cry Toxins and Insects - Liu, Lu; Li, Zhou; Luo, Xing; Zhang, Xia; Chou, Shan-Ho; Wang, Jieping; He, Jin (Frontiers in Microbiology, 2021)
In this article, we review the latest works on the insecticidal mechanisms of Bacillus thuringiensis Cry toxins and the resistance mechanisms of insects against Cry toxins. Currently, there are two models of insecticidal mechanisms for Cry toxins, namely the sequential binding model and the signaling pathway model. In the sequential binding model, Cry toxins are activated to bind to their cognate receptors in the mid-intestinal epithelial cell membrane, such as glycophosphatidylinositol (GPI)-anchored aminopeptidases-N (APNs), alkaline phosphatases (ALPs), cadherins, and ATP transporters to form pores that elicit cell lysis, while in the signaling pathway model, the activated Cry toxins first bind to the cadherin receptor, triggering an extensive cell signaling cascade to induce cell apoptosis. However, these two models cannot fully describe the complexity of insecticidal process of Cry toxins, and new models are required. Regarding the resistance mechanism of insects against Cry toxins, the main method bacteria employed is to reduce the effective binding of Cry toxins to their cognate cell membrane receptors by gene mutations, epigenetic mechanisms, to reduce the expression levels of the corresponding receptors by trans-regulation. Moreover, the host intestinal microbiota, and detoxification enzymes also play significant roles in the insects’ resistance against Cry toxins. Today, high-throughput sequencing technologies like transcriptomics, proteomics, and metagenomics are powerful weapons for studying the insecticidal mechanisms of Cry toxins and the resistance mechanisms of insects. We believe that this review shall shed some light on the interactions between Cry toxins and insects, which can further facilitate the development and utilization of Cry toxins.